(3JfhjQ GdZHT aj aVd GdShOGf hGdMHTs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ENJGQ ef LejY GdeNdhbGJ GdEfSGf Ke EUWai efg Cgd GdJbi hGdEjeGf Ke LYd eMd fXQI GdbdhH GdHGH GdChd ai PcQ ef JfSH Edjg GdShOGf s
(3BNQgG (B:s
(3hNP Edi GdNjQ HfGUjJi hGLYd GdESdGe efJgi QVGi Gddge Efi VYja abhfi hEfi Pdjd aGYR Hi hCfi abjQ aCZffi fLR GdcJGH HMeO Gddg hYhfg s
(3HChdg JedcGJ heWGdYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B501s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJGQjNs